1999
DOI: 10.1046/j.1432-1327.1999.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements of para‐alkylphenols to bind to estrogen receptor

Abstract: Octyl-and nonylphenols in the environment have been proposed to function as estrogens. To gain insight into their structural essentials in binding to the estrogen receptor, a series of phenols with saturated alkyl groups at the para position, HO-C 6 H 4 -C n H 2n+1 (n = 0±12), were examined for their ability to displace [ 3 H]17b-estradiol in the recombinant human estrogen receptor, which was expressed in Sf9 cells using the vaculovirus expression system. All tested para-alkylphenols were found to bind fully t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 31 publications
1
53
0
1
Order By: Relevance
“…One of the toxicological implications for the delay of excretion of nonylphenol and nonylphenol-glucuronide is estimated to the binding to and inhibition of ER (Tabira et al, 1999); another is the inhibition of MRP-2 which excretes various glucuronides such as estradiol glucuronide (Ito et al, 2001) and bilirubin glucuronide (Kusuhara et al, 1998). The delay of nonylphenol excretion is possible because of the adverse effects of nonylphenol on rat reproductive systems (Laws et al, 2000).…”
Section: Fig 5 Excretion Of Alkylphenol Metabolites During Liver Pementioning
confidence: 99%
“…One of the toxicological implications for the delay of excretion of nonylphenol and nonylphenol-glucuronide is estimated to the binding to and inhibition of ER (Tabira et al, 1999); another is the inhibition of MRP-2 which excretes various glucuronides such as estradiol glucuronide (Ito et al, 2001) and bilirubin glucuronide (Kusuhara et al, 1998). The delay of nonylphenol excretion is possible because of the adverse effects of nonylphenol on rat reproductive systems (Laws et al, 2000).…”
Section: Fig 5 Excretion Of Alkylphenol Metabolites During Liver Pementioning
confidence: 99%
“…1), and it has been suggested that alkylphenols may act as endocrine disrupters by mimicking the activity of 17␤-estradiol at estrogen receptors. Indeed, in a variety of cells transfected with human estrogen receptors, alkylphenols have been shown to bind weakly and provoke modest estrogenic effects (15)(16)(17). Conversely, alkylphenols have been reported to promote estrogenic signaling by inhibiting androgen receptor activation in some tissues (18,19).…”
mentioning
confidence: 99%
“…Only compounds with a 6-10 carbon chain were active, with potencies ranging from 100 nM to 3 M. In addition, the conversion of the hydroxy group on the phenol moiety to a methyl led to a complete loss of activity. Furthermore, the analogous hexyl, heptyl, octyl, and nonyl-phenols reported to be micromolar estrogen receptor ligands were evaluated (Tabira et al, 1999). As expected, they display low-affinity estrogen receptor agonism but, more importantly, lacked any crossover activity at the SF-1 receptor (data not shown).…”
Section: Resultsmentioning
confidence: 86%